2021
DOI: 10.3390/diagnostics11101931
|View full text |Cite
|
Sign up to set email alerts
|

Dominating Cause of Pulmonary Hypertension May Change Over Time—Diagnostic and Therapeutic Considerations in a Patient with Pulmonary Hypertension Due to Rheumatoid Arthritis with Lung Involvement

Abstract: Chronic lung diseases are one of the most frequent causes of pulmonary hypertension (PH). The diagnostic challenge is to differentiate PH due to chronic lung disease from pulmonary arterial hypertension (PAH) with coexisting chronic lung disease. Moreover, the dominating cause of PH may change over time, requiring the implementation of new diagnostic procedures and new treatment modalities. We present a 68-year-old female, initially diagnosed with PH in the course of interstitial lung disease, with restrictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…One of the main causes of PH is a disease of the connective tissue, and RA is the most common disease of the connective tissue. However, compared with connective tissue diseases such as scleroderma, mixed connective tissue disease, and dermatomyositis/polymyositis, the prevalence of PAH in RA patients is lower 7 . According to Fayed et al's analysis of the various forms of PAH associated with connective tissue diseases, patients with RA often develop postcapillary PAH 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main causes of PH is a disease of the connective tissue, and RA is the most common disease of the connective tissue. However, compared with connective tissue diseases such as scleroderma, mixed connective tissue disease, and dermatomyositis/polymyositis, the prevalence of PAH in RA patients is lower 7 . According to Fayed et al's analysis of the various forms of PAH associated with connective tissue diseases, patients with RA often develop postcapillary PAH 8 …”
Section: Discussionmentioning
confidence: 99%
“…Even a single example, RA‐associated PH, illustrates the complexity of disease development. At the onset of the disease, interstitial lung disease predominated PH, whereas PAH occurred later in the course of the disease 7 . Even a small increase in pulmonary artery pressure can lead to a marked increase in PAS 12 …”
Section: Discussionmentioning
confidence: 99%
“…PAH is a life-threatening complication associated with CTD, particularly in systemic sclerosis and systemic lupus erythematosus. RA is the most common CTD, but the prevalence of PAH in patients with RA is lower than that in patients with CTDs such as scleroderma, mixed collagen tissue disease, and dermatomyositis/polymyositis[ 17 ]. Fayed et al [ 18 ] provided an overview of CTD-associated PAH types and reported that post-capillary PAH is most common in patients with RA, while lung disease-associated PAH is commonly seen in patients with IIM and sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fayed et al [ 18 ] provided an overview of CTD-associated PAH types and reported that post-capillary PAH is most common in patients with RA, while lung disease-associated PAH is commonly seen in patients with IIM and sarcoidosis. The case of RA-associated PAH presented by Szturmowicz et al [ 17 ] illustrates the complexity of PAH in a single individual, with ILD-PAH dominating the early stage and CTD-PAH developing later.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the prothrombotic effect associated to chronic inflammation increases the risk of venous thromboembolism ( 62 ), and chronic thromboembolic pulmonary hypertension should be taken into account when approaching to the differential diagnosis of pulmonary hypertension in patients with RA and RA-ILD. Interestingly, the dominating cause of pulmonary hypertension may change over time, making the diagnostic and therapeutic process more challenging ( 63 ).…”
Section: Introductionmentioning
confidence: 99%